The Role of Atmospheric Blocking in Regulating Arctic Warming - Cheng You; Michael Tjernström; Abhay Devasthale; Daniel Steinfeld (Geophysical Research Letters)
Abstract Using ERA5 reanalysis we find positive trends in poleward transport of moisture and heat during 1979–2018 over the winter Barents Sea sector and summer East Siberian Sea sector. The increase in blocking occurrence (blocking days) can explain these trends. Blocking occurrence over the Barents Sea sector significantly increased in the last 40 winters, inducing increasingly stronger poleward transport of moisture and heat. The high linear correlation between poleward energy transports and temperature over the Barents Sea sector suggests that poleward energy transports dominate the regional warming trend there. Meanwhile, in summer, more frequently occurring blocking over the Beaufort Sea sector causes a positive trend of poleward moist and heat transport over the East Siberian Sea sector. The high linear correlation between the blocking occurrence and temperature suggests that the increasing shortwave radiation and subsidence within the more frequently occurring blocking contribute to the regional warming trend.